2010
DOI: 10.7326/0003-4819-152-8-201004200-00007
|View full text |Cite|
|
Sign up to set email alerts
|

Cumulative Incidence of False-Positive Test Results in Lung Cancer Screening

Abstract: National Cancer Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 40 publications
0
116
0
5
Order By: Relevance
“…10), which dictates that many individuals require follow-up examinations and a substantial proportion of individuals undergo unnecessary thoracotomy (18). A recent manuscript by the Lung Screening Study reported that up to 7% of patients who were screened by CT underwent some level of invasive procedure (19). This suggests that a test with a higher specificity than CT that can identify high-risk individuals with early-stage disease would be a valuable aid to the early detection of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…10), which dictates that many individuals require follow-up examinations and a substantial proportion of individuals undergo unnecessary thoracotomy (18). A recent manuscript by the Lung Screening Study reported that up to 7% of patients who were screened by CT underwent some level of invasive procedure (19). This suggests that a test with a higher specificity than CT that can identify high-risk individuals with early-stage disease would be a valuable aid to the early detection of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the International Commission on Radiological Protection indicated three male or six female cases of radiation-induced cancer would occur in every 100,000 screened individuals over 15-20 years [33]. Recent estimates have suggested the falsepositive rate of CT varied from 10 to 42 %, compared with 3 to 19 % for CXR [34,35]. As a less radioactive method than CT, but much more sensitive than CXR, DR may integrate both of the advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Up to one-third of all CT scans require some type of follow-up imaging [24][25][26], which further increases the risks of the reactions noted above and of the patient potentially developing cancer in the future secondary to the radiation from the imaging. Incidental findings can also increase a patient's anxiety and fear, and the evaluation of incidental findings may require that additional procedures be performed-again exposing the patient to various risks and requiring further investments of time, energy, and money.…”
Section: The Most Commonly Requested Imaging Tests In Primarymentioning
confidence: 99%